Education About Plastic Waste into Fuel in Bingkeng Village, Dayeuhluhur Sub-District, Cilacap Regency - Muhammad Alwi, Rizky Nur; Budiana, Rundy; Nurul Aeni, Tri Hana; Hidayah, Tika Nur; Triyansyah, Muhammad Dinar; Yunisa, Kathy; Safitri, Gina Sani; Ubaidillah, Andri; Aprilia, Anisya Bunga; Nur Awaliyah, Cucu; Anggarasari, Nandhini Hudha (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
Plastic is one of the materials that are widely used in everyday life, because it has advantages including strong, light and stable. But the plastic on the market today is a synthetic polymer made from petroleum that is difficult to decompose. This platic waste is very much a complex problem in this bingkeng village environment because in 2020 in bingkeng village there is plastic waste of 1ton.Therefore we aim to conduct extension of plastic waste treatment tools so that the community tau plastic waste treatment can be used as fuel oil (BBM) can also be made vaving block from the results of the waste burning of plastic waste and useful also for the community in the preconomics sector. Counseling activities were conducted in September 2021 in Bingkeng village, inviting community leaders as many as 29 participants participated in extension activities.